If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -27) + 3(x + 3) = 9x + -59 Reorder the terms: -1(-27 + x) + 3(x + 3) = 9x + -59 (-27 * -1 + x * -1) + 3(x + 3) = 9x + -59 (27 + -1x) + 3(x + 3) = 9x + -59 Reorder the terms: 27 + -1x + 3(3 + x) = 9x + -59 27 + -1x + (3 * 3 + x * 3) = 9x + -59 27 + -1x + (9 + 3x) = 9x + -59 Reorder the terms: 27 + 9 + -1x + 3x = 9x + -59 Combine like terms: 27 + 9 = 36 36 + -1x + 3x = 9x + -59 Combine like terms: -1x + 3x = 2x 36 + 2x = 9x + -59 Reorder the terms: 36 + 2x = -59 + 9x Solving 36 + 2x = -59 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 36 + 2x + -9x = -59 + 9x + -9x Combine like terms: 2x + -9x = -7x 36 + -7x = -59 + 9x + -9x Combine like terms: 9x + -9x = 0 36 + -7x = -59 + 0 36 + -7x = -59 Add '-36' to each side of the equation. 36 + -36 + -7x = -59 + -36 Combine like terms: 36 + -36 = 0 0 + -7x = -59 + -36 -7x = -59 + -36 Combine like terms: -59 + -36 = -95 -7x = -95 Divide each side by '-7'. x = 13.57142857 Simplifying x = 13.57142857
| 24y-(y-27)=1(y-54) | | 200x^4=-800x^3+9000x^2 | | 100=-16t^2-20t+436 | | 1+4x-21x^2=0 | | 2y+7y=180 | | C=38.48+0.50x | | 2w(w+2)=0 | | 8(p-1.25)=4(2p-0.5) | | 105x^2-238x+105=0 | | x+0.5=-0.16666 | | 5+r/(-2)=-6 | | 14y^2=180 | | (2x^-3y^2)^-4/(2x^2y)^-3 | | y=-4x/1 | | y=4x/1 | | 3log(2x)+4=7 | | x^3+11x^2+18=0 | | 6n+21=57 | | sin^2x-3sinx-10=0 | | ln(9x-8)=6 | | 7x-4+6x=7x+35-7x | | 13(t-5)+5t=6(3t+3)-13 | | 36u^2=9u | | -6X+13+7X=-2 | | -.45(40)+.8X=.3(40+X) | | 2(-10)+5y=10 | | 4w+3w-6w-6w=w+15+2w-31 | | 1-5x=13+x | | 4g^2+2g+3=0 | | 4X+8-3X=3 | | 2y+6=8+3y | | (x-2)(3x+5)= |